If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 26 = 10x + -10 Reorder the terms: 26 + 5x = 10x + -10 Reorder the terms: 26 + 5x = -10 + 10x Solving 26 + 5x = -10 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 26 + 5x + -10x = -10 + 10x + -10x Combine like terms: 5x + -10x = -5x 26 + -5x = -10 + 10x + -10x Combine like terms: 10x + -10x = 0 26 + -5x = -10 + 0 26 + -5x = -10 Add '-26' to each side of the equation. 26 + -26 + -5x = -10 + -26 Combine like terms: 26 + -26 = 0 0 + -5x = -10 + -26 -5x = -10 + -26 Combine like terms: -10 + -26 = -36 -5x = -36 Divide each side by '-5'. x = 7.2 Simplifying x = 7.2
| -3h+-h+6h+7h=15 | | 8x-4+4x+28=5x+10 | | 2y=3+6y | | 14p+3p-17p+p+p=20 | | 900n-360=0 | | 8x-4=5x+10 | | 8x-4+5x+10=4x+28 | | 5(x+3)+8=-2(x-8) | | 3r+-16r+9r=4 | | 8x-4=5x+10+4x+28 | | 3r+16r+9r=4 | | -4j+10=-8j-10 | | 6+2x-5=8x+37-2x | | 19r-18r+3r-3r=15 | | 9x=-13x+9 | | -6y+6=-3y | | 42.3=3x | | 16h-12h=12 | | 2b-b=17 | | 2b-4(b-4)=b+3 | | 5(x-2)=2(x+5)+10 | | 4x^2-19x+5=0 | | 4-5x=-3x | | -2w+4=4w-8 | | 11(2x-1)=8(2x+1)+11 | | 9x+3=-8x+12-5x | | 3x+2y-2(5x-4y)= | | 8r-5r+2=9r+2-r | | 3(3x+1)=-4(2x-3)-5x | | -66-7x=-13x+18 | | (5x+3x)+(7x+3)= | | (a-5)(5a-1)= |